Analysis of prognostic factors in diffuse large B-cell lymphoma associated with rheumatic diseases - Vadim Gorodetskiy; Natalya Probatova; Tatiana Obukhova; Vladimir Vasilyev (Lupus Science and Medicine)
Objective The risk of developing diffuse large B-cell lymphoma (DLBCL) is increased in many rheumatic diseases (RDs). It is possible that RD-associated DLBCL is a distinct subset within the category of ‘DLBCL’, exhibiting characteristic biological features and clinical behaviour. However, information on RD-associated DLBCL is limited.Methods We searched the V.A. Nasonova Research Institute of Rheumatology (Russia) database from 1996 to 2021 for patients with RDs and coexisting DLBCL. Prognostic factors including the International Prognostic Index (IPI), bulk disease and c-MYC/8q24 gene rearrangements were analysed. Furthermore, we stratified DLBCLs as germinal centre B-cell (GCB) subtype and non-GCB subtype based on Hans’ immunohistochemical algorithm and also examined Epstein-Barr virus (EBV) status.Results Twenty-seven patients with RD-associated DLBCL were identified. Twenty patients had primary Sjogren’s syndrome, three had systemic lupus erythematosus, two had rheumatoid arthritis and two had systemic sclerosis. Secondary Sjogren’s syndrome was found in four patients. The median age at the time of diagnosis of DLBCL was 59 years with a female predominance (26:1). Based on IPI, 16 patients were assigned to the intermediate-high and high-risk groups. Bulk disease was detected in 29% of patients. Of the 20 examined cases, 4 (20%) were classified as the GCB subtype and 16 (80%) were classified as the non-GCB subtype. EBV was detected in 2 of the 21 tested cases (10%), and the c-MYC/8q24 gene rearrangement was not found in any of the 19 examined cases. After the lymphoma diagnosis, the median overall survival (OS) was 10 months (range: 0–238 months).Conclusions Except for the more common non-GCB subtype, we did not identify any other prognostic factor that could influence the prognosis of patients with RD-associated DLBCL. We believe that short OS in our patients was predominantly associated with decreased tolerance to lymphoma treatment.